2020
DOI: 10.1111/psyp.13521
|View full text |Cite
|
Sign up to set email alerts
|

Acute psychological stress promotes general alertness and attentional control processes: An ERP study

Abstract: The current study investigated the influence of acute psychological stress on selective attention processes. After an acute stressor or a control condition, 20 participants performed an arrow‐based version of the Eriksen flanker task, while ERPs (N1, N2, P3), reaction times, accuracy, subjective stress, and electrocardiogram signal were measured. Results showed elevated self‐report stress, negative affect, state anxiety, heart rate, and reduced high‐frequency heart rate variability in the stress block than in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
32
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 70 publications
5
32
1
1
Order By: Relevance
“…Shackman et al ( 2011 ) found that N1 was related to the perceptual process, which indicated that the level of alertness and sensory input were significantly increased under the threatening condition. Qi and Gao ( 2020 ) found that acute psychological stress increased general alertness and promoted attentional control in selective attention processes. In the stress condition in the current study, the participants had to use cognitive resources to deal with the stress process of alertness, and at the same time, use attention resources to participate in the motion-in-depth perception task.…”
Section: Discussionmentioning
confidence: 99%
“…Shackman et al ( 2011 ) found that N1 was related to the perceptual process, which indicated that the level of alertness and sensory input were significantly increased under the threatening condition. Qi and Gao ( 2020 ) found that acute psychological stress increased general alertness and promoted attentional control in selective attention processes. In the stress condition in the current study, the participants had to use cognitive resources to deal with the stress process of alertness, and at the same time, use attention resources to participate in the motion-in-depth perception task.…”
Section: Discussionmentioning
confidence: 99%
“…ERP studies on stress' effect on response inhibition also showed that stress could amplify the early premotor response inhibition represented by N2 and enhance the cognitive control process (Dierolf, Fechtner, Böhnke, Wolf, & Naumann, 2017;Qi, Gao, & Liu, 2017). Additionally, the flanker task has been consistently used to investigate selective attention and has shown a facilitation effect reflected in N2 under stress (Qi, & Gao, 2020). Overall, previous studies have suggested that stress could enhance the general attentional control process and promote the motivational selective attention processing.…”
Section: Introductionmentioning
confidence: 96%
“…However, the unique and unusual social ecology brought about by COVID-19 warrant examining rumination as a consequence of COVID-19 stressors. Rumination has been documented to be influenced by perceived stress ( Chen and Huang, 2019 , Wang et al, 2019 ) and because attention increases under high levels of vigilance ( Qi & Gao, 2020 ), the cognitive behavior presents itself as a natural, but potentially dangerous, variable in models of stress consequences ( Nolen-Hoeksema et al, 2008 ) for adolescents ( Skitch & Abela, 2008 ). Specifically, rumination has been evidenced to be a mutable variable in response to stressful life events (e.g., Li et al, 2019 , Liu and Wang, 2017 , Michl et al, 2013 ) and can play a mediating role between changing stressors and their respective consequences, such as work stressors and impaired sleep (​ Berset, Elfering, Lüthy, Lüthi, & Semmer, 2011 ) and perceived stress and depression ( Wang et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%